Original species identification of Epimedii Folium (Epimedium) and their distributional responses to climate change - Yiheng Wang; Kangjia Liu; Meng Li; Yuran Bai; Chengcai Zhang; Binbin Yan; Wenpan Dong; Yan Zhang; Jiahui Sun (Science of Traditional Chinese Medicine)
Abstract. Background. Epimedii Folium is well known for its medicinal value. Four Epimedium species—Euphorbia brevicornu, E. sagittatum, E. pubescens, and E. koreanum—are the designated original plants of Epimedii Folium. Objective. The objective of this study is to facilitate the identification of the four Epimedium species and clarify their distributional responses to climate change. Methods. In this study, we assessed the genetic divergence of the four species and identified the molecular markers for species identification by using chloroplast genome sequences. Furthermore, we forecasted the distribution of potentially suitable regions of the four species Folium under climate change. Results. The authors obtained 26 chloroplast genome sequences of the four species and identified 1393 variable sites and 273 indel events. Genetic divergence analyses revealed that E. koreanum had long genetic distance from the other three species. Compared with the complete chloroplast genome, six hypervariable markers were discovered, and both rps4-trnL and ndhF were chosen as Epimedii Folium-specific DNA barcodes. Climate change is expected to influence the geographical distribution of the four Epimedium species, which were primarily found in China, South Korea, and Japan, leading to both expansion and contraction of their distribution ranges. Conclusion. Two identification markers were selected as the specific DNA barcodes for all four original plant species of Epimedii Folium. In addition, the shift of potential suitable area in various climate scenarios has been predicted. With the support of identification markers and the dynamics of suitable distribution areas, we are able to establish a foundation for the sustainable utilization of medicinal Epimedium resources in the future.